Modeling the Joint Train Timetabling and Track Maintenance Planning Problem Using Constraint Programming - Maciej HOJDA (Communications of International Proceedings, 2021)
In this paper considered is a train timetabling and a track maintenance planning problem. To provide a high quality of railway service, the providers have to consider two types of maintenances: unplanned, resulting from unforeseen disturbances, such as critical infrastructure failures, and planned, which include regular conservation work. The problem of the paper is to incorporate maintenance tasks in an already existing schedule in a way that keeps the resulting timetable mostly unchanged. This allows for continuous, uninterrupted operation of a railway network without degrading the quality of the service. Formulation of a joint decision making problem uses the methods of constraint programming. Application of the no-overlap type of constraints results in a compact form of the formulation and allows to use solution methods dedicated to constraint programming problems.
Keywords: Train timetabling; Maintenance planning; Constraint programming.